(untitled) (Research, Society and Development, 2021)
Bone fracture, undoubtedly, is one of the main problems associated with the increase in the population’s life expectancy. Mainly, femoral fractures, which require surgical treatment in order to reduce the fracture by osteosynthesis. In case of severe impairment on the proximal epiphysis femoral, complete joint replacement by a total hip implant is recommended. Hip arthroplasty is a procedure widely applied in medicine; however, several implant failures have been reported. This study aimed to present, through a literature review, the main causes that lead total hip implants to failure in use and to elucidate corrective measures to avoid such failures. The leading causes of implant failures identified were: fatigue, loosening, metallosis, in addition to disability and disease related to the patient’s profile. In conclusion, a multidisciplinary team shall design osteosynthesis devices. This team needs knowledge and expertise in medical science, engineering design, and material selection. The main purpose is to achieve optimized design parameters to reduce the risk of failure and prevent accidents, therefore avoiding resubmitting the individual to a new surgical correction procedure.